Unique Evolution of Symbiobacterium thermophilum Suggested from Gene Content and Orthologous Protein Sequence Comparisons. (6th December 2010) - Oshima, Kenro; Ueda, Kenji; Beppu, Teruhiko; Nishida, Hiromi
Abstract : Comparisons of gene content and orthologous protein sequence constitute a major strategy in whole-genome comparison studies. It is expected that horizontal gene transfer between phylogenetically distant organisms and lineage-specific gene loss have greater influence on gene content-based phylogenetic analysis than orthologous protein sequence-based phylogenetic analysis. To determine the evolution of the syntrophic bacterium Symbiobacterium thermophilum, we analyzed phylogenetic relationships among Clostridia on the basis of gene content and orthologous protein sequence comparisons. These comparisons revealed that these 2 phylogenetic relationships are topologically different. Our results suggest that each Clostridia has a species-specific gene content because frequent genetic exchanges or gene losses have occurred during evolution. Specifically, the phylogenetic positions of syntrophic Clostridia were different between these 2 phylogenetic analyses, suggesting that large diversity in the living environments may cause the observed species-specific gene content. S. thermophilum occupied the most distant position from the other syntrophic Clostridia in the gene content-based phylogenetic tree. We identified 32 genes (14 under relaxed selection and 18 under functional constraint) evolving under Symbiobacterium -specific selection on the basis of synonymous-to-nonsynonymous substitution ratios. Five of the 14 genes under relaxed selection are related to transcription. In contrast, none of the 18 genes under functional constraint is related to transcription.